Mechanical behaviour of aluminium alloy foams modelled with X-ray microcomputed tomography - Heitor, Diogo Couto (2021)
In recent years, there has been an increase in interest in cellular materials for structural applications, especially cellular metals (e.g., metal foams made of aluminium and its alloys). These closed-cell and open-cell foams usually have complex cellular structures resulting from the foaming process and their mechanical properties are governed by their cellular structures and by the properties of the base material. However, their mechanical characterization is difficult and most of the times can result in the destruction of the foam specimen. In this study, X-ray microcomputed tomography (µCT) was used together with finite element modelling to develop numerical models to estimate the elastic moduli and evaluate the effects of processing of the information obtained with the µCT scans in the final results. Such a technique complements experimental testing and brings great versatility. In order to accomplish this task, different thresholding techniques (segmentation) were applied to the 2D slices, which are the result of µCT scans, with special focus on a manual global technique with the mass as a quality indicator. Then, some reconstruction algorithms (e.g. Marching Cubes 33) were used to create 3D tessellated models in the STL format, which were oversampled (excessive number of faces) and with errors. Therefore, a simplification/clean-up procedure was applied to solve those issues, being analysed in terms of mass maintenance, shape maintenance with the Hausdorff algorithm and face quality, i.e., face aspect ratio. Two different procedures were evaluated, with and without small structural imperfections, so that the impact of the procedures could be analysed as well as the effect of the presence of small defects. The results obtained were evaluated and compared to several analytical and theoretical models, models based on representative unit-cells and experimental results in terms of the relation between the relative density and the relative Young’s modulus. Results demonstrated that the developed procedures were very good at minimizing changes in mass and shape of the geometries while providing good face quality, i.e., face aspect ratio. The models were also shown to be able to predict the properties of metallic foams in accordance with the findings of other researchers. In addition, the process of obtaining the models and the presence of small structural imperfections were shown to have a great impact on the final results.